Acesso à informação geográfica: reflexões sobre a importância das Infraestruturas de Dados Espaciais (IDE) nas políticas públicas - Alencar, Cely Martins Santos de [UNESP]; Santos, Plácida Leopoldina Ventura Amorim da Costa [UNESP] (My University, 2013)
This article discusses the access to geographic information and its importance for the public policies formulation, reflecting on the implementation of the Spatial Data Infrastructure. The data view and the maps construction are useful for identifying needs and sponsoring public managers in decision making. The public policies implementation stages are optimized when the quantitative and qualitative information are integrated to the spatial phenomena relations. The improvement in the use of geographic information for decision making will be achieved when spatial data are efficiently generated in spatial data infrastructures.

O presente artigo discute o acesso à informação geográfica e sua importância na formulação de políticas públicas, refletindo sobre a implantação da Infraestrutura de Dados Espaciais (IDE). A visualização dos dados e a construção de mapas são úteis na identificação de demandas e para subsidiar os gestores públicos na tomada de decisão. As fases de implementação das políticas públicas são otimizadas quando as informações quantitativas e qualitativas estão integradas as relações dos fenômenos espaciais. Progressos na utilização de informação geográfica para a tomada de decisão serão alcançados quando os dados espaciais forem gestados eficientemente em infraestruturas de dados espaciais.
Geographic information access: thoughts on the importance of spatial data infrastructures in public policy
Keywords: Dados geográficos; informação geográfica; Informação e tecnologia